國際化過程與組織規模：集團企業調節效果 - 林玟廷; Wen-Ting Lin (國立交通大學, 2016)
本研究從資訊處理觀點探討公司國際化過程（速度與廣度），對其組織規模之影響。同時探討公司隸屬的集團企業之型態如何影響國際化與組織規模之間的關係。本研究以九個年度（2000年至2008年）772家上市企業年度資料為樣本，採用固定效果GLS迴歸模型驗證假說，實證結果顯示國際化速度與國際化廣度對組織規模呈現正向顯著影響；而且當公司為友誼型集團企業之隸屬公司，將強化國際化過程對組織規模之正向關係，當公司為家族型集團企業之隸屬公司，將弱化國際化過程對組織規模之正向關係。本研究貢獻在於連結公司國際策略與組織理論領域研究。

Based on the information-processing perspective, this article examines the relationship between the pace and scope of firm internationalization and organizational size. Additionally, as contextual variables, for example, business groups may have a moderating influence on organizational size. The analysis involves a sample of 772 publicly listed firms in Taiwan over a period of nine years (2000-2008). The findings indicate that the pace and scope of internationalization positively influence organizational size. It is also observed that when a firm is affiliated with a business group based on friendship, the relationship between the pace and scope of firm internationalization and organizational size will be positively moderated, and when a firm is affiliated with a family business group, the relationship between the pace and scope of firm internationalization and organizational size will be negatively moderated. This research contributes to the literature linking corporate strategy in firm internationalization with organizational theory.
Internationalization Processes and Organizational Size: The Moderating Effects of Business Groups
Keywords: 友誼型集團企業; 家族型集團企業; 國際化速度; 國際化寬度; 組織規模; Friendship Business Group; Family Business Group; Internationalization Pace; Internationalization Scope; Organizational Size